Pengaruh Konflik dalam Ketidakadilan Gender di Rumah Tangga pada Film Pendek Memorial Karya Achmad Sulchan - Umniyyah, Zahratul; Rido, Hamdan (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2023)
Gender injustice within households is often reproduced through power relations, honor norms, and socially legitimized constructions of masculinity. The short film Memorial by Achmad Sulchan represents domestic conflict rooted in gender inequality and the normalization of symbolic violence. This study aims to analyze the influence of gender injustice–based conflict within households as represented in the film. A qualitative approach was employed using media text analysis and visual narrative analysis. Data were collected through systematic observation of scenes, dialogues, and narrative structures, and analyzed using theories of honor culture, power relations, and gender representation in media. The findings indicate that domestic conflict in the film is shaped by masculine dominance, honor-based legitimization of violence, and media’s role in reproducing unequal gender norms. These results demonstrate that Memorial not only reflects social reality but also serves as a critical commentary on patriarchal culture that sustains gender injustice. This study contributes to film studies, gender studies, and media analysis by highlighting the critical role of short films as instruments of social reflection.